Neuropsychological effects of mobile phones and base stations - Kulo?lu, Murat; Korkmaz, Sevda (Istanbul Universitesi, 2011)
The mobile phones which are evolving and becoming increasingly common since the beginning of twentieth century and almost indispensable in our lives are important communication tools. Mobile phones have been greatly extended the service area by the recent technological developments. The number of base stations has increased quite to offer this service better, depending on the service to meet increasing demand and to extend the coverage area due to commercial concerns. With this increase, the possible dangerous effects on the human health of the exposure to electromagnetic radiation emitted from mobile phones and base stations, especially neuropsychological effects, raises a general worry in the community. This situation has resulted in a detailed examination to explore the short and long term effects of radiofrequency waves in many clinical studies. Electromagnetic waves emitted from mobile phones and base stations has been shown short-term effects on cognitive function and mainly headaches, sleep disorders and anxiety symptoms. There is a limited number of studies which are showing the long-term relationships between neuropsychological disturbances and these changes. Most of the studies reported different results with each other, and contradictory, and therefore there is no consensus on this issue. Our goal, in light of recent data in the literature, is to draw attention to the importance of this issue on the public health by examining the neuropsychological effects that may develop as a result of chemical and thermal effects of electromagnetic radiation.
Cep telefonu ve baz istasyonlarının nöropsikolojik etkileri
Keywords: Base station; Electromagnetic waves; Mobile phone; Radiation